Effect of fruit load on yield and quality of peach (Prunus persica) in mid hills of Sikkim Himalaya - KUMAR, ASHOK; AVASTHE, R K; PANDEY, BRIJESH; LEPCHA, BONIFACE; RAHMAN, H (The Indian Journal of Agricultural Sciences, 2012)
Manual fruit thinning had a significant influence on both yield and fruit quality. Retaining 75 fruits/plant produced better shaped fruits, good yield and without severe fall in the quality could be recommended for two years old plants of peach var. Shan-e-Punjab in the mid hills of Sikkim Himalayas. The fruit yield increased with increase in the number of fruits retained/tree with concurrent decrease in fruit quality.